The effectiveness of music therapy for the treatment of Alzheimer's disease - Dominka Rehan; Joanna Szydziak; Aleksandra Hrapkowicz; Kinga Janowska; Olga Szeidl; Julia Wołoszczak; Julia Wołoszczak; Agnieszka Mioskowska; Daria Dąbkowska (Journal of Education, Health and Sport)
Introduction: Alzheimer’s disease (AD) is a progressive neurodegenerative disorder and the most prevalent cause of dementia. It is caused by the degeneration of brain cells due to the accumulation of intracellular hyperphosphorylated tau - containing neurofibrillary tangles and extracellular plaques of amyloid-beta peptide. While pharmacotherapy remains the main form of treatment (including cholinesterase inhibitors and antagonists to NMDA), various non-pharmacological therapy modalities have gained increasing attention as complementary treatment options, such as music therapy.